Reflections of communities of practice and its technologies on organization, sustainability development: an exploratory study: oil and gas companies in northern Iraq. - Hasan , Iman; Abdulmuhsin, Amir (Humanities Journal of University of Zakho, 2022)
In societies and corporate organizations, sustainable development, particularly organizational sustainability, is receiving greater prominence and importance. Because these concepts give organizations, stakeholders, and society, a competitive advantage and adds value. However, sustainability is not fully integrated at the strategic, tactical and operational level. The lack of understanding of the mechanisms that create value and how to retain it in all parts of the value chain, because parts of this chain require significant coordination and cooperation, is thought to be the biggest barrier to implementing sustainability in organizations. The technologies of communities of practice (CoPs), which are presented in our research, are one of the most important mechanisms that may be employed to improve organizational sustainability. The proposed model for the link between these concepts in Iraqi oil industry enterprises was tested using structural equation modeling. The use of communities of practice's technologies and organizational sustainability's components had a direct and significant influence, according to preliminary research findings. The paper also indicated that experts and engineers within CoPs must pay attention to the criteria for selecting acceptable technologies for use in these CoPs that give them the ability to sustain business in organizations